Kepercayaan Diri Mahasiswa Aktif Organisasi - Wan Chalidaziah; Muhammad Nasir; Nuraida Nuraida (Prodi Bimbingan dan Konseling Islam, 2021)
This study aims to determine the level of self-confidence in students based on their organizational experience. This study uses a comparative quantitative method. The population of the study was IAIN Langsa students who participated in the organization as many as 119. Then, a sample was drawn using the proportional random sampling technique with a total sample of 92 students. The research instrument used is a self-confidence scale of 25 statement items with r = 0.836. Furthermore, the data were analyzed using the One Way ANOVA test with the help of SPSS 20. The results showed that overall the self-confidence of students who participated in the organization was in the high category and there was a significant difference in self-confidence when viewed from the experience gained in joining the organization.